Effects of Open and Closed Chain Exercises on Dynamic Balance and Range of Motion in Patients with Knee Osteoarthritis: RCT - Muhammad Ehtisham ul Haq Raza, Zainab Hassan, Wishal Edwin, Sidra Faisal, Fiza Saleem, Mashar Hayyat (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Osteoarthritis is a combination of mechanical problems characterized by degradation of articular cartilage, articulating joints and subchondral space. Aim: To compare the effects of open chain kinetic exercises and closed kinetic chain exercises in improving dynamic balance and range of motion in patients with knee osteoarthritis. Study Design: Randomized controlled trial. Methodology: Study was conducted at Chugtai Medical center Lahore and sample of 46 patients were recruited and were randomly allocated in two groups. One group performed OKC exercises and the other group was asked to perform CKC exercises, while both of the groups received a common baseline treatment prior to corresponding intervention. Two session a week were given for a period of one month. Goniometry and Y-balance scale were used to assess ROM and dynamic balance pre and post treatment, respectively. Data was evaluated by using SPSS version 23. Results: In this study, the intra-group analysis illustrated that the increase in range of motion and improvement in dynamic balance was statistically significant in both groups with p-value<0.05. Whereas, the inter-group analysis showed that both interventions were clinically effective in treating knee osteoarthritis with p-value>0.05 during the treatment session of four weeks. Practical Implication: This study highlighted that physical training that includes open kinetic chain (OKC) and closed kinetic chain (CKC) exercises were found to be effective in improving balance and in increasing range of motion by reducing pain among osteoarthritis patients. Conclusion: It was concluded that patients with OKC exercises have shown equal improvement in ROM and dynamic balance compared to those who have been treated with CKC exercises. Keywords: Osteoarthritis, Exercises and Dynamic Balance.